Functional interrelation of MYC2 and HY5 plays an important role in Arabidopsis seedling development. (24th June 2019) - Chakraborty, Moumita; Gangappa, Sreeramaiah N.; Maurya, Jay P.; Sethi, Vishmita; Srivastava, Archana K.; Singh, Aparna; Dutta, Siddhartha; Ojha, Madhusmita; Gupta, Nisha; Sengupta, Mandar; Ram, Hasthi; Chattopadhyay, Sudip
Summary: Arabidopsis MYC2 bHLH transcription factor plays a negative regulatory role in blue light (BL)‐mediated seedling development. HY5 bZIP protein works as a positive regulator of multiple wavelengths of light and promotes photomorphogenesis. Both MYC2 and HY5, belonging to two different classes of transcription factors, are the integrators of multiple signaling pathways. However, the functional interrelations of these two transcription factors in seedling development remain unknown. Additionally, whereas HY5‐mediated regulation of gene expression has been investigated in detail, the transcriptional regulation of HY5 itself is yet to be understood. Here, we show that HY5 and MYC2 work in an antagonistic manner in Arabidopsis seedling development. Our results reveal that HY5 expression is negatively regulated by MYC2 predominantly in BL, and at various stages of development. On the other hand, HY5 negatively regulates the expression of MYC2 at various wavelengths of light . In vitro and in vivo DNA–protein interaction studies suggest that MYC2 binds to the E‐box cis ‐acting element of HY5 promoter. Collectively, this study demonstrates a coordinated regulation of MYC2 and HY5 in blue‐light‐mediated Arabidopsis seedling development. Significance Statement: The functional inter‐regulation of three transcription factors, MYC2, HY5 and CAM7, remains unknown in Arabidopsis seedling development. This study demonstrates a mechanistic view on coordinated regulation of these proteins in Arabidopsis seedling development.